2023
DOI: 10.31925/farmacia.2023.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment – Reviewing Methods of Assessment and Improvement

Abstract: According to the World Health Organization (WHO), adherence is considered "the extent to which a person's behaviourtaking medication, following a diet, and/or executing lifestyle changes corresponds with agreed recommendations from a health care provider". Adherence rates average 50% in countries such as the United States, exerting important pressure on health systems. Factors which influence medication adherence can be related to the patient, the clinical conditions, therapy, socioeconomic factors and the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…[21,22] Our findings are however at variance with some other previous studies which reported that pharmacy refill record was not a reliable method of adherence determination. [23] Of note, this finding is valid only for closed-pharmacy systems [24] where patients access medications from only one source, and the Nigerian National ARV programme is implemented as a closed-pharmacy system where patients can only pick-up ARVs from the pharmacy at the treatment center where they are registered.…”
Section: Discussionmentioning
confidence: 99%
“…[21,22] Our findings are however at variance with some other previous studies which reported that pharmacy refill record was not a reliable method of adherence determination. [23] Of note, this finding is valid only for closed-pharmacy systems [24] where patients access medications from only one source, and the Nigerian National ARV programme is implemented as a closed-pharmacy system where patients can only pick-up ARVs from the pharmacy at the treatment center where they are registered.…”
Section: Discussionmentioning
confidence: 99%